Reflective and Democratic Education in “Freedom Writers” (2007): A Deweyan Perspective for Current Indonesian Education - Anisa, Rizka Sakinatun; Farla Syifa Azzahra; Ivana Salsabila Rahmawati; Mochamad Alfat Rafif Yumna; Endang Fauziati (Universitas Cokroaminoto Palopo, 2026)
This study examines the portrayal of John Dewey’s principles of reflective and democratic education in Freedom Writers and explores their relevance to contemporary educational developments in Indonesia. Employing a qualitative research design, the study uses content analysis as the primary method to examine themes of teaching and learning presented in the film. The analysis focuses on selected scenes, dialogues, and classroom interactions that reflect instructional practices and pedagogical values. The findings reveal that Erin Gruwell’s instructional approach closely reflects Dewey’s core educational principles. Her teaching practices emphasize experiential learning, reflective activities that support students’ understanding, and the creation of a democratic classroom environment that promotes active participation, personal expression, and mutual respect. These practices are consistent with Dewey’s view that education should be rooted in learners’ lived experiences and social interaction. This study highlights the relevance of Freedom Writers in supporting Indonesia’s ongoing shift toward a more humanistic, experiential, and student-centered educational paradigm. Furthermore, it demonstrates the potential of films as pedagogical resources that can help educators understand and apply educational philosophies within authentic classroom contexts.